Developmental changes in human megakaryopoiesis. (12th September 2013) - Bluteau, O.; Langlois, T.; Rivera‐Munoz, P.; Favale, F.; Rameau, P.; Meurice, G.; Dessen, P.; Solary, E.; Raslova, H.; Mercher, T.; Debili, N.; Vainchenker, W.
Summary: Background: The molecular bases of the cellular changes that occur during human megakaryocyte (MK) ontogeny remain unknown, and may be important for understanding the significance of MK differentiation from human embryonic stem cells (hESCs) Methods: We optimized the differentiation of MKs from hESCs, and compared these with MKs obtained from primary human hematopoietic tissues at different stages of development. Results: Transcriptome analyses revealed a close relationship between hESC‐derived and fetal liver‐derived MKs, and between neonate‐derived and adult‐derived MKs. Major changes in the expression profiles of cell cycle and transcription factors (TFs), including MYC and LIN28b, and MK‐specific regulators indicated that MK maturation progresses during ontogeny towards an increase in MK ploidy and a platelet‐forming function. Important genes, including CXCR4, were regulated by an on–off mechanism during development. Discussion: Our analysis of the pattern of TF network and signaling pathways was consistent with a growing specialization of MKs towards hemostasis during ontogeny, and support the idea that MKs derived from hESCs reflect primitive hematopoiesis.